Pemilihan Student of the month dengan Metode Simple Additive Weighting (SAW) dan Metode Weighted Product (WP) berbasis web - Rizaldi, Muhammad Indra; Makhsun, Makhsun; Hindasyah, Achmad (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Every 1 (one) month SMK Nusantara 1 Tangerang City gives awards to its students. The award was given in the form of student of the month in order to increase the enthusiasm of learning students at SMK Nusantara 1 Tangerang City. The student of the month selection process is initiated by the principal with consideration from the vice principal and also the heads of expertise programs. However, until now the student of the month selection process still has a manual process that does not take into account the characteristics of the assessment criteria. Therefore, this study aims to evaluate the use of Simple Additive Weighting (SAW) method and Weighted Product (WP) method in the decision support system for the selection of student of the month. This research can help school principals in selecting student of the month more objectively. From this study obtained a final result of 0.994 for the SAW method and 0.050 for the WP method and stated that the student with the largest total score was Arminanda Khansa Sadiya.